Hemoperitoneum in a Cirrhotic Patient Due to Rupture of Retroperitoneal Varix. (23rd April 2009) - Sincos, Igor Rafael; Mulatti, Grace; Mulatti, Sheila; Sincos, Ilana Cristina; Belczak, Sergio Q.; Zamboni, Valdir
Abstract : The rupture of retroperitoneal varices is a rare and catastrophic complication of portal hypertension. We describe a case of this nature, the first in Brazilian medical literature, and also reviewing all previous 34 cases. We systematically analyzed all therapeutic approach and propose a management algorithm for diagnosis and treatment of this lethal condition. The majority of the patients presented with abdominal pain, distention and hypotension, and developed hemorrhagic shock. Rupture of retroperitoneal varices can be properly managed if an early diagnosis is made and surgery is performed promptly, which is the only effective treatment. Arteriography should be used when the suspicion is of rupture of hepatocellular carcinoma.